2014
DOI: 10.4028/www.scientific.net/amr.875-877.1265
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Inert Gas Atomisation of Cr-Mn-Ni Austenitic Steel Alloys

Abstract: The Cr-Mn-Ni austenitic steel cast alloys containing 16 wt.-% chromium, 7 wt.-% manganese and 3 to 9 wt.-% nickel are used as matrix material to manufacture TRIP-Matrix-Composite containing MgO partially stabilised ZrO2ceramics. In the present work, these steel master alloys were atomised via a vacuum inert gas atomisation to provide fine grain sized metal powders for the assembling of TRIP-Matrix-Composite. The atomised steel powders where characterised according to their chemical composition and the d50mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Centrifugal atomization uses the centrifugal force of rotating electrodes or discs to disperse molten material feed for droplet breakup 12 . Vacuum or soluble gas atomization uses the supersaturation of molten material feed by a soluble gas to induce atomization in a vacuum environment 13,14 . Ultrasonic atomization uses agitation of liquid material film or atomizing fluid by ultrasonic vibration to induce droplet breakup 15 .…”
Section: Working Principles Of Atomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrifugal atomization uses the centrifugal force of rotating electrodes or discs to disperse molten material feed for droplet breakup 12 . Vacuum or soluble gas atomization uses the supersaturation of molten material feed by a soluble gas to induce atomization in a vacuum environment 13,14 . Ultrasonic atomization uses agitation of liquid material film or atomizing fluid by ultrasonic vibration to induce droplet breakup 15 .…”
Section: Working Principles Of Atomizationmentioning
confidence: 99%
“…12 Vacuum or soluble gas atomization uses the supersaturation of molten material feed by a soluble gas to induce atomization in a vacuum environment. 13,14 Ultrasonic atomization uses agitation of liquid material film or atomizing fluid by ultrasonic vibration to induce droplet breakup. 15 Atomization methods are commonly employed in the current market to produce fine spherical alloy powder.…”
Section: Types Of Atomization Routementioning
confidence: 99%
“…Examining obtained PSD values, manufactured powders remain in a range of typical values for this atomization unit under comparison to previously published works. [45,46] Korobeinikov et al [46] reported that d50 decreases by enhancing of the spraying temperature and decrease in the spraying rate. Nevertheless, these tendencies are not fully realized in the current study.…”
Section: Powder Size Distribution and Particles Morphologymentioning
confidence: 99%